Adaptation level, management value and productivity of large white sows of hungarian origin in the steppe zone of Ukraine - Khalak, Viktor; Халак, Віктор Іванович; Horchanok, Anna; Horchanok, A.; Horchanok, A. V.; Горчанок, Анна Володимирівна; Kuzmenko, Oksana; Кузьменко, Оксана Анатоліївна; Lytvyschenko, L.; Litvischenko, L. O.; Litvischenko, Lіudmyla; Lytvyschenko, L. O.; et al. (University of Agronomic Sciences and Veterinary Medicine of Bucharest, Romania – Faculty of Animal Science Engineering and Management, 2022)
The paper presents the results of a study of long-term adaptation, management value and productivity of Large White sows of Hungarian origin in the conditions of steppe zone of Ukraine. It was found that Large White sows of Hungarian origin are characterized by high rates of long-term adaptation, management value and reproductive qualities. Thus, their age of life is 44.1 ± 1.97 months (Cv = 35.27%); the duration of breeding use is 32.8 ± 1.95 months (Cv = 46.91%); the index "level of adaptation" varies in the range from 5.48 to 27.20 points. Taking into account the intrabreed differentiation according to the index "level of adaptation", a significant difference between the groups of sows of class M + and M- was found according to the following indicators: "farrowing received", "live piglets in total, heads", "multifetation, heads", "nest weight during the weaning at the age of 28 days, kg". The indicator "livability of piglets before weaning at the age of 28-32 days, %" in the experimental groups of sows ranges from 90.1 to 94.4%. Sows from the category "high management value" exceeded peers from the category "low management value" in terms of "farrowing received", "live piglets in total, heads", "multifetation, heads", "nest weight during the weaning at the age of 28-32 days, kg" by 46.67% on average. The indicator "livability of piglets before weaning at the age of 28-32 days, %" in different management value groups of sows ranges from 91.3 to 100.0%. The maximum increase in additional products was obtained from sows which index "level of adaptation" ranges from 5.48 to 8.20 points (+4.99%), as well as from animals of the category "high management value" (+3.41 %), respectively. These indicators are proposed to be used as criteria for selection of highly productive animals in the controlled population. У статті наведено результати дослідження довготривалої адаптації, цінності господарювання та продуктивності свиноматок великої білої породи угорського походження в умовах степової зони України. Встановлено, що свиноматки угорського походження характеризуються високими показниками тривалої адаптації, господарської цінністю та репродуктивними якостями. Таким чином,вік життя 44,1±1,97 місяця (Cv =35,27%); тривалість племінного використання становить 32,8±1,95 місяців (Cv =46,91%); індекс «рівень адаптації» коливається в діапазоні від 5,48 до 27,20 балів. З урахуванням внутрішньо породності диференціація за індексом «рівень адаптації», достовірна різниця між групами свиноматок клас М+ та М- встановлено за такими показниками: «отримано опорос», «всього живих поросят, голів», «багатоплідність, голів», «маса гнізда при відлученні у віці 28 днів, кг». Показник «життєздатність поросят до відлучення у віці 28-32 дні %" у дослідних групах свиноматок коливається від 90,1 до 94,4%. Свиноматки від категорія «висока управлінська цінність» перевищила аналогів з категорії «низька управлінська цінність». «отримано опорос», «всього живих поросят, голів», «багатоплідність, голів», «маса гнізда під час відлучення в рр. 28-32 дні, кг» в середньому на 46,67 %. Показник «життєздатність поросят до відлучення у віці 28-32 дні, %» у різних господарських групах цінність свиноматок коливається від 91,3 до 100,0%. Максимальне збільшення продукції отримано від свиноматок, індекс «рівень адаптації» яких коливається від 5,48 до 8,20 балів (+4,99%), а також як від тварин категорії «висока господарська цінність» (+3,41 %) відповідно. Ці показники пропонується скласти використовували як критерії відбору високопродуктивних тварин у контрольовану популяцію.
Рівень адаптації та експлуатаційна цінність свиноматок великої білої породи угорської селекції в умовах степової зони України
Горчанок Анна Володимирівна https://orcid.org/0000-0003-0103-1477 Литвищенко Людмила Олександрівна http://orcid.org/0000-0002-4239-5405
Keywords: variability; мінливість; adaptation; адаптація; breed; порода; correlation; співвідношення; economic efficiency; економічна ефективність; management value; господарське значення; reproductive qualities; відтворювальні якості; sow; свиноматка